Teori pilihan rasional untuk memahami koruptor di Indonesia - Choky R. Ramadhan (Komisi Pemberantasan Korupsi, 2023)
Rational choice theory is used and developed to explain crime, criminals, crime prevention, and punishment (deterrent effect). According to this theory, criminals rationally consider the pleasure and suffering they will gain from committing a crime. Various theoretical and empirical studies have then developed factors that influence the rationality of criminals. This article details a collection of studies on rational choice theory and relates them to crimes of corruption. Literature on corruption crimes and efforts to prevent and eradicate them is often related to rational choice theory. Additionally, this article attempts to use rational choice theory to understand the perpetrators of corruption crimes in Sukamiskin Prison. This research is exploratory and uses dozens of unannounced inspection videos, interviews with offenders, publicly available news reports, and interviews with several parties who have visited Sukamiskin Prison. Sukamiskin Prison was chosen as a location of interest because the inmates who had been convicted of corruption crimes (corruptors) continued to engage in corrupt practices in the prison. Understanding the reasons and patterns of corruption can enrich our understanding of crimes of corruption in Indonesia using rational choice theory.